MODEL PEMBELAJARAN PAI DI SEKOLAH SEBELUM, SAAT, DAN SESUDAH PANDEMI - Sogianor Sogianor; Syahrani Syahrani (CV. ADIBA AISHA AMIRA, 2022)
With the rapid development of the internet and digital information technology and coupled with a pandemic, humans need to adapt and change many aspects of their lives, including in the learning process, especially when there is a strong urge to adapt technology more quickly due to the ongoing pandemic outbreak. Learning that was previously done outside the network is now taking place online during a pandemic. The disruption that has occurred in the learning process throughout the pandemic will certainly not restore the habits that existed in learning before the pandemic when the pandemic ends. Actually every normal before the disruption will change to normal after the disruption.